An AHP-Evaluation Models for Ranking Construction Tenders Using Simulation: A Case Study in Kurdistan Region of Iraq - Fatah, Khwazbeen Saida; Ahmed, Swar Omer (Sulaimani Journal for Pure and Applied Sciences, 2015)
In ranking decision alternatives, Analytic Hierarchy Process is regarded as one of the most successful techniques to deal with multiple criteria decision making problems. Recognizing that tender evaluation is a typical multi-criteria decision making problem, this paper introduces an evaluation approach based on AHP methodology for ranking various alternative options, each represents a construction project the tender, and then selecting the best one. The proposed model can guide decision makers in construction industry identify contractors with the best potential to deliver satisfactory outcomes in a final process of tender selection in Kurdistan Region of Iraq. Moreover, in order to reduce the inherent uncertainty within the AHP, which may significantly affect the decision process, a new methodology is proposed by using simulation. This model is tested by a hypothetical scenario where six tenders are evaluated and then, the best candidate is selected. Furthermore, the criteria used for the tender selection in the model and the significance of each criterion had been arrived at by conducting the first survey study for public and private organizations in Kurdistan Region of Iraq.
Keywords: Analytic Hierarchy Process; Uncertainty; Tender Selection Process; Kurdistan Region of Iraq